Pengaruh Budaya Organisasi, Komunikasi, dan Motivasi terhadap Kinerja Karyawan Love, Bonito Indonesia - Febrina, Christy; Amelia, Tifa Noer (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This study aims to determine whether there is a relationship between organizational culture, work communication, and motivation with employee performance at Love, Bonito Indonesia. The independent variables in this study are organizational culture, work communication, and motivation while the dependent variable is the performance of employees of Love, Bonito Indonesia. This research was conducted at Love, Bonito Indonesia with 20 respondents. This type of research is quantitative research. Methods of data collection using questionnaires and data analysis using simple linear regression. The results of the study partially show that organizational culture has a positive and significant effect on employee performance, but for communication and motivation partially it has no effect on employee performance. Simultaneously organizational culture, communication, and motivation affect employee performance.